2008
DOI: 10.1101/gad.1725808
|View full text |Cite
|
Sign up to set email alerts
|

Modular control of endothelial sheet migration

Abstract: Growth factor-induced migration of endothelial cell monolayers enables embryonic development, wound healing, and angiogenesis. Although collective migration is widespread and therapeutically relevant, the underlying mechanism by which cell monolayers respond to growth factor, sense directional signals, induce motility, and coordinate individual cell movements is only partially understood. Here we used RNAi to identify 100 regulatory proteins that enhance or suppress endothelial sheet migration into cell-free s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

20
299
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 259 publications
(321 citation statements)
references
References 45 publications
20
299
2
Order By: Relevance
“…Contrary to previous work (22,(24)(25)(26)29), these cells form neither 2D sheets nor 3D structures, nor are they highly polarized, and their single-cell migratory behavior is established (13,14,16). The microfluidic cell culture platform hosts independent and isolated culture conditions in each of the isolated 96 polymethylsiloxane (PDMS) chambers (34-nL volume) that mimic physiological conditions more plausibly than traditional cell-culture environments in which concentrations of, for instance, secreted signaling molecules are diluted into large volumes of surrounding fluid.…”
contrasting
confidence: 54%
See 1 more Smart Citation
“…Contrary to previous work (22,(24)(25)(26)29), these cells form neither 2D sheets nor 3D structures, nor are they highly polarized, and their single-cell migratory behavior is established (13,14,16). The microfluidic cell culture platform hosts independent and isolated culture conditions in each of the isolated 96 polymethylsiloxane (PDMS) chambers (34-nL volume) that mimic physiological conditions more plausibly than traditional cell-culture environments in which concentrations of, for instance, secreted signaling molecules are diluted into large volumes of surrounding fluid.…”
contrasting
confidence: 54%
“…Previous work on single-cell migration has focused on isolated (11)(12)(13)(14)(15)(16)(17)(18)(19)(20) or strongly polarized and aligning (21,22) cell types, mostly using population-averaged bulk assays (23) or simple observations in a social context (2,3). However, strongly cross-correlated cell motion and collective substrate deformation has been found to arise in mechanically interlinked cells transmitting forces through both cell-cell linkages and the substrate (24)(25)(26)(27)(28)(29). These studies revealed useful information on cell migration, but because in general the relevant interactions in a social context and their relative importance are not established, migratory behavior of cells in a social context remains as one of the major unresolved problems in biology (30).…”
mentioning
confidence: 99%
“…Uniform ligand, or no ligand, could therefore give directional signaling output if a group is not free but organized in an inherently polarized manner. This effect could be responsible for, or contribute to, directional cell movement in other types of collective migration-for example, sheet or slug migration in tissue culture models or in vivo (6,17).…”
Section: Discussionmentioning
confidence: 99%
“…This selection method identified 91 shRNAs that accelerated or impaired migration (Tables 1 and 2). Sixty-two of the 91 identified target genes have been previously associated with cell migration by RNAi screen [8][9][10]13,16 (Supplementary Tables 2 and 3). The remaining 29 target genes had not been previously identified as cell migration regulators by RNAi screen.…”
Section: Genome-wide Functional Selection Of Cell Migration Regulatorsmentioning
confidence: 99%
“…shRNA libraries have been used to perform genetic screens in tissue culture cells for a variety of phenotypes 7 . Recent studies have analysed the closures of scratches in cellular monolayers after growth factor stimulation, using siRNA library targeting kinase and phosphatase genes 8,9 . siRNA-based screening was performed to identify regulators of multiple cell adhesion complex formation 10 , and RNAi screening to identify inhibitors of cell migration using SKOV-3 cells (a highly motile ovarian carcinoma cell line) 11 .…”
mentioning
confidence: 99%